Financing of Dengue Hemorrhagic Fever Control Program in Banda Aceh City - Ellia Nufara; Ali Ghufron Mukti; Tri Baskoro T. Satoto Mail (JMMR (Jurnal Medicoeticolegal dan Manajemen Rumah Sakit), 2018)
Background: From January to June 2017, the number of DHF cases in Banda Aceh City reached 216 cases with the incidence Rate of 89.5%. To suppress the increase in the cases, the Health Office of Banda Aceh and its staff has conducted control activities, but the number of DHF cases is difficult to reduce. It is therefore necessary to conduct this study to assess the relationship between the availability of DHF control programs and the number of DHF cases in Banda Aceh City. Methods: This observational was done using a case-control study design. The number of samples was 76 cases in four selected health centers with a case-control ratio of 1:1. For data collection, it was conducted in July until August 2017. Results: The results show that the reduction in funding of DHF disease control programs was associated with an increase in the number of DHF cases in Banda Aceh City (p = 0.005, OR = 2.49 at 95% CI; 1.23 - 5.06). Conclusion: Inadequate financing can increase the number of DHF cases in Banda Aceh City.